CURRENT STATUS, CHALLENGES AND PREVENTIVE STRATEGIES TO OVERCOME DATA INTEGRITY ISSUES IN THE PHARMACEUTICAL INDUSTRY - M., VIGNESH; G. N. K., GANESH (International Journal of Applied Pharmaceutics, 2020)
The pharmaceutical industry is currently one of the most dynamic among all industries. At present, it is striking with various compliance challenges like never before there is increased regulation, acquisitions, push toward harmonization and endemic in a Data Integrity (DI) concern. DI weakness is identified, either as a result of an audit or a regulatory inspection, companies with multiple sites should ensure that appropriate corrective and preventive actions are implemented across the organizations and appropriate notification to regulatory authorities should be made wherever applicable. The objective of the study carries the number of issues involved within data integrity in current GMP aspects, the root causes were addressed based on warning letters. This review intends to study the concept of data integrity holistically in all aspects, regulatory expectations and to evaluate the state of compliance and challenges that explore to suggest appropriate remedial and proactive measures to avoid DI issues. There were many challenges involved to overcome the issues, which are all about the one's handling by maintaining good documentation practice. The importance, strategies and recommendations were discussed to overcome from the repeated data integrity mistakes. This review was carried out by systematic searches of data integrity in relevant guidelines, published articles, reviews and abstracts in Google scholar, Pubmed, Science direct, Embase, Web of science, Cochrane database of systematic reviews of articles up to March 2020. The keywords used for gathering information were listed below.